A systematic review of the predictive value of 18F‐fluoro‐2‐deoxyglucose positron emission tomography on survival in locally advanced rectal cancer after neoadjuvant chemoradiation. (November 2013) - Krug, B.; Crott, R.; de, L.; D'Hondt, L.; Vander Borght, T.
Abstract Aim Treatment of locally advanced rectal cancer (LARC) includes preoperative radiation therapy with or without chemotherapy followed by radical surgery, but the clinical outcome is uncertain. A systemic review was carried out to determine the predictive value of 18F‐fluoro‐2‐deoxyglucose positron emission tomography (18FDG‐PET) for assessing disease‐free (DFS) and overall survival (OS) in LARC. Method A literature search (PubMed/MEDLINE, EMBASE, Cochrane) up to January 2012 to identify full papers with sequential 18FDG‐PET and survival data, using indexing terms and free text words. The inclusion criteria were: a study of at least 10 patients, having sequential 18FDG‐PET imaging before and after adjuvant chemoradiation and a minimal follow‐up of 24 months. Studies were selected by two of the authors. A meta‐analysis was performed for DFS and OS using the hazard ratio (HR) as the primary outcome. Results Five eligible studies were identified including 330 patients (mean age 63 years, 64% men), in which PET‐CT or PET imaging was used. The American Joint Committee on Cancer stage distribution was as follows: Stage I, 2%; Stage II, 44%; Stage III, 52%; Stage IV, 1%. The pooled HRs for complete metabolic response versus partial or no response were 0.39 (95% CI 0.18–0.86; P = 0.02) for OS and 0.70 (95% CI 0.16–3.14; P = 0.64) for DFS. The lack of significance for DFS might be explained by different follow‐up characteristics. There was also clinical heterogeneity among the different studies. Conclusion This systematic review indicates that complete metabolic response on sequential 18FDG‐PET data after preoperative chemoradiation of LARC is predictive of OS, but not of DFS.